Effect of Habitat Heterogeneity on Organic Matter in Tropical Dry Deciduous Forest - Sajiwan Kumar; Lalji Singh (Journal of Soil and Water Conservation, 2022)
Habitat heterogeneity was evaluated in terms of patchy availability of organic matter in tropical dry deciduous forest in Barnawapara wild life Sanctuary Ratpur, Chhattisgarh, India. The forest floor had a distribution of troughs in which litter accumulated. These depressions differed in appearance from the adjoining areas or flats. The organic matter availability in the soil of forest floor and to assess the effect of habitat heterogeneity on organic matter in relation to the topographic differences and microsites (Depression and Non-depression). Significant variations in soil organic matter along microsites in three different habitats (hill base, mid slope, hill top) were observed. Highest value of organic matter presents in depression micro-sites as compared to non-depression microsites. It ranged from 1.56 % to 1.93 % under all three habitats across three seasons. The differences in organic matter due to interaction of habitats microsites found also statistically significant (P<0.05%). It was ranged from 0.91 % to 2.45 %. Highest was found under hill top depression whereas lowest in hill base non-depression microsites.